Evaluation of Temperature Increase From Joule Heat in Numerical Tooth Model by Applying 500 kHz Current for Apical Periodontitis Treatment—Effect of Applied Voltage and Tooth Conductivity. Issue 3 (4th February 2021) - Tarao, Hiroo; Akutagawa, Masatake; Emoto, Takahiro; Takei, Amane; Yumoto, Hiromichi; Tominaga, Toshihiko; Ikehara, Toshitaka; Kinouchi, Yosuke
Abstract : For apical periodontitis treatments, a new method with the insertion of an electrode into the root canal of a tooth and application of a current at 500 kHz to sterilize the area by Joule heat has attracted attention. However, few studies have quantified the temperature increase in the root canal. This study aimed to investigate the basic characteristics of the temperature increase in a simple and standard tooth model when energizing a current at 500 kHz to the numerical tooth model with typical electrical and physical properties. We developed a numerical model of a standard tooth (dentin) and periodontal tissues consisting of an alveolar bone, cortical bone, and gingiva, and physiological saline in a root canal and calculated the temperature increase inside the numerical model by a coupled analysis of current and heat when a voltage was applied across the electrodes. The calculated results for the different applied voltages showed a temperature increase at the apical portion of the root canal, which increased with the applied voltage even for the same total supplied energy. The temperature increase occurred at the apical portion of the root canal as the tooth conductivity decreased. When the tooth conductivity was high, a current passed through the dentin, which led to a decrease in the temperature at the apical portion of the root canal. However, a chemical solution with a higher conductivity in the root canal tended to increase the temperature at the apical portion of the root canal, regardless of the tooth conductivity. More efficient approaches for increasing the spatial and temporal temperature for the tooth model target are needed. © 2021 Bioelectromagnetics Society.